The Influence of Combining Intelligent English Education with Sports on Students' Positive Psychological Construction - Guo Liu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The research purpose was to check the impact of combining intelligent English education with sports on student’s positive psychological construction. The researcher selected 500 students from 10 ordinary universities in a certain province, including 250 humanities students and 250 science students, among the 2021 freshmen. A comprehensive survey was conducted on these 500 freshmen using the SCL-90 scale and commonly used physical exercise methods questionnaire to understand their mental health status and the physical exercise methods they usually use. The research results indicate that physical exercise has a positive impact on the mental health problems of college students. Physical exercise can enhance physical fitness and lay a good foundation for mental health; it can enhance self-confidence and to some extent overcome inferiority complex; Physical exercise can effectively improve interpersonal relationships and reduce loneliness; In addition, physical exercise can also change the mind-set of college students and overcome anxiety and sadness. Therefore, the study concludes that mental health is an important foundation for college students to adapt to social development needs and achieve personal development. Sports have the function of enhancing physical fitness and promoting the development of mental health and have important value for the mental health of college students. The findings of this study emphasize the positive impact of sports on the mental health of college students, providing useful information for educational decision-makers and practitioners. These results support the inclusion of sports in the education system, promoting students' positive psychological construction through a combination of intelligent English education and physical exercise, and helping them better adapt and develop during their university years.